Use of Microwave Radiation for Activating Carbon from Rice Husk Using ZnCl2 Activator - Arnelli Arnelli; Ulya Hanifah Henrika Putri; Fandi Nasrun Cholis; Yayuk Astuti (Jurnal Kimia Sains dan Aplikasi, 2019)
Activated carbon is one of the most commonly used adsorbents in a variety of separation processes because it is inexpensive, and also the design and principal of application are quite simple. The ability of activated carbon as an adsorbent is related to its large surface area and pore volume, varying pore structure, and diverse surface reactivity. The use of microwave radiation can further improve the efficiency of activated carbon adsorption. Micro-waves can affect the pore texture and surface of the activated carbon, but rarely do both practitioners and researchers control these variables influencing the relationship between features and performance of biomass-based activated carbon as an adsorbent at the time of manufacture from the initial stage (carbonation) to carbon application active (e.g., adsorption of heavy metals, surfactants, and organic molecules). This study aims to synthesize activated carbon from rice husk, which has the efficiency and capacity of adsorption of heavy metals such as Pb and activator organic molecules used is ZnCl2 30% and microwave radiation. This research has succeeded in making activated carbon using the ZnCl2 activator and microwave radiation. The time and power of microwave radiation that provides the highest efficiency in the carbon activation process for Pb ion adsorbate, were 7 minutes and 800 W. For phenol adsorbate was 5 minutes at 800 W. The highest efficiency time and concentration of adsorption for Pb ion adsorbate were 40 minutes at 60 ppm while for phenol adsorbate were 5 hours at 100 ppm. The adsorption efficiency for Pb cation adsorbate was 99.57%. While for phenol adsorbate is 81.05%. Characterization with FTIR, SEM-EDX, and SAA showed a C-Cl bond, the pores were visible, and an increased surface area of activated carbon was 36.9 times the surface area of carbon and the pores formed were mesoporous.